Der älteste sicher einzustufende Fund des modernen Elchs Alces alces (LINNAEUS, 1758) in Mitteleuropa - Marzia, Breda; Ingo, Raufuss (Landesamt für Bergbau, Geologie und Rohstoffe (LBGR), 2016)
The earliest central European remain of Alces alces is described from the Late Saalian site of Jaenschwalde near Cottbus, Germany. The paleogeographic distribution of modern moose, Alces alces, is discussed as well as its coexistance with the last representative of the related species, Cervalces latifrons.